2017
DOI: 10.3389/fnhum.2017.00561
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Association between Tendency to Forgive and Spontaneous Brain Activity in Healthy Young Adults

Abstract: The tendency to forgive (TTF) refers to one's global dispositional level of forgiveness across situations and relationships. Previous brain imaging studies examined activation patterns underlying forgiving process, yet the association between individual differences in the TTF and spontaneous brain activity at resting-state remains unknown. In this study, resting-state functional magnetic resonance imaging (fMRI) was used to investigate the correlation between the TTF and spontaneous brain activity in a young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Research that examined brain structures underlying forgiving responses showed that higher tendency to forgive scores were positively correlated with the gray matter volume in the dorsolateral prefrontal cortex, a brain area that plays a significant role in envisioning others’ feelings and showing empathy; the tendency to forgive was negatively related to the gray matter volume in the right insular cortex and inferior frontal gyrus, indicating being more forgiving [ 35 , 36 ]. Studies on the effects of mindfulness practice indicated that focusing on the present moments could increase the hippocampus’ gray-matter density (a brain area important for learning and memory) and decrease it in the amygdala, the emotional center playing an important role in causing anxiety and stress [ 37 ].…”
Section: Results Regarding the Strategies To Build Resiliencementioning
confidence: 99%
“…Research that examined brain structures underlying forgiving responses showed that higher tendency to forgive scores were positively correlated with the gray matter volume in the dorsolateral prefrontal cortex, a brain area that plays a significant role in envisioning others’ feelings and showing empathy; the tendency to forgive was negatively related to the gray matter volume in the right insular cortex and inferior frontal gyrus, indicating being more forgiving [ 35 , 36 ]. Studies on the effects of mindfulness practice indicated that focusing on the present moments could increase the hippocampus’ gray-matter density (a brain area important for learning and memory) and decrease it in the amygdala, the emotional center playing an important role in causing anxiety and stress [ 37 ].…”
Section: Results Regarding the Strategies To Build Resiliencementioning
confidence: 99%
“…Since Fenell (1993) found that forgiveness is integral to a long-lasting marriage, forgiveness has received increasing attention from researchers because of its positive influence on marital quality and marital stability via the adaptive process by mending inevitable injuries and transgressions (e.g., Fenell, 1993 ; McCullough et al, 1998 ; McNulty, 2008 ; David and Stafford, 2015 ). Despite there is a lack of consensus on the definition of forgiveness, researchers agree that forgiveness involves a prosocial changing process toward the transgressor ( McCullough et al, 2001 ; Li and Lu, 2017 ), in which negative motivation (e.g., unforgiveness) decrease and positive emotions increase ( McCullough et al, 2003 ; Fincham et al, 2005 ). While several scholars proposed that the forgiveness process incorporates an intellectual decision to forgive, as well as an emotional forgiveness component ( Enright, 1996 ; Strelan and Covic, 2006 ), empirical evidence in respect to the different roles between decisional and emotional forgiveness on marital stability is rare.…”
Section: Introductionmentioning
confidence: 99%
“…The task-activated functional MRI (fMRI) study reported higher activity in multiple areas (pink) when participants were instructed to forgive compared with when they were instructed to not forgive offenders (12). The resting-state fMRI study reported that higher scores on the tendency to forgive scale (i.e., more likely to forgive transgressions by others) were negatively correlated with spontaneous activity (amplitude of low frequency fluctuation [ALFF]) in regions associated with mentalizing and self-referential processing (blue) (13). In the absence of studies on selfforgiveness, the neural correlates of loving kindness meditation may be informative.…”
mentioning
confidence: 99%
“…An fMRI study of experienced meditators reported that loving kindness meditation (compared with resting-state) resulted in both increases (left medial and anterior prefrontal cortices) and decreases (left parieto-occipital cortex) in activity (14). It is noteworthy that the areas of decreased activity partially overlap with areas in which lower resting-state activity correlated with higher forgiveness (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation